Microbiological evaluation of environmental cleanliness in haematopoietic cell transplant patient rooms: implementing JACIE standards. Issue 3 (March 2020) - Zeneli, A.; Petrini, M.; Foca, F.; Bernabini, M.; Ronconi, S.; Montalti, S.; Pancisi, E.; Soldati, V.; Golinucci, M.; Frassineti, G.L.; Altini, M.
Summary: Background: Environmental hygiene is one of the most important strategies to prevent hospital-acquired infections by reducing pathogens in haematopoietic cell transplant (HCT) patient rooms. This study was designed in response to JACIE requirements for microbiological monitoring, and aimed to assess environmental hygiene in protective isolation rooms. Methods: Environmental cleanliness was assessed by measuring microbial loads in at-rest and operational conditions sampled from target surfaces, and in passive and active air from rooms occupied by patients with different grades of neutropenia. The study also evaluated whether microbial loads were influenced by isolation precautions. Results: The failure rate of cleanliness on target surfaces in at-rest conditions was 0% compared with 37% for surfaces and 13% for passive and active air samples in operational conditions. Differences in failure rates were observed in the rooms of patients with different levels of neutropenia ( P =0.036 for surfaces, 0.028% for passive air). No relationship was found between infections and microbial loads. Conclusions: Microbiological assessment integrated with an enhanced monitoring programme for hospital hygiene provides invaluable information to drive infection control policies in HCT patients. These results highlight the need to set and validate strict standards for the assessment of cleanliness in a clinical setting.